Preparation and fabrication of NiCo coated TiO2-NTs for hydrogen evolution - Uzal, Hasan; Döner, Ali; Bayrakçeken, Hüseyin (Bellwether Publishing, Ltd., 2021)
Hydrogen production via water splitting is a very attractive way using effective electrocatalysts. One of the effective electrocatalysts that are used in water splitting is NiCo alloys. In this study, highly ordered titanium dioxide nanotubes (TiO2-NTs) are firstly prepared by electrochemical anodization method in terms of being a substrate material for NiCo coatings. Hydrogen evolution behaviors of three types of NiCo coated TiO2-NTs are investigated in 1 M KOH solution at room temperature. Coated surfaces are characterized by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), and cyclic voltammetry (CV). HER activities of NiCo coated TiO2-NTs are investigated by cathodic current–potential curves, electrochemical impedance spectroscopy (EIS), and electrolysis process. The stability of NiCo-coated TiO2-NTs is also investigated. Results show that TiO2-NTs surface leads to large surface area and high porosity for NiCo nano-particles and thus, HER performance of coatings increases. NiCo-coated TiO2-NTs improves the catalytic HER activity in terms of current density, hydrogen volume, polarization resistance (Rp), and conductivity. Enhanced HER activity can be based on the boosted surface area, conductivity, and more active sites for hydrogen ion adsorption as well as synergistic effects.
Keywords: electrocatalysis; Electrolysis; NiCo coatings; Titanium dioxide nano-tubes; Water splitting